Analisis Karakteristik Pengeringan dan Sifat Fisik Kimia Teh Herbal Kulit Buah Naga Merah dengan Variasi Irisan Ketebalan dan Suhu Pengeringan - Tamba, Yesinta Kristin; Yulianti, Ni Luh; Gunadnya, Ida Bagus Putu (Jurnal Ilmiah Teknologi Pertanian Agrotechno, 2023)
The processing of red dragon fruit skin into herbal tea is to use ingredients as drinks and can be accepted by the public. This management makes the harvest durable in the drying process. This study aims to find out the Drying Characteristics and Chemical Properties of Red Dragon Fruit Skin Herbal Tea With Variations in Thickness Slices and Drying Temperature. This study was compiled using (CRD) with two factors, namely the drying temperature factor (50 o C, 60 o C and 70 o C) and the slice thickness factor (3mm and 5mm). There were 6 treatment interactions and the treatment was repeated three times to obtain 18 units of bandages. The data from the study results were analyzed using ANOVA and continued with the DMRT test at a level of 5%. The observed measures consist of sensible heat, moisture content, ash content, and organoleptics. The results showed that the interaction of drying temperature and thickness slices in the red dragon fruit skin herbal tea had a noticeable impact in the size of sensible heat, moisture content, ash content, color, taste and aroma. The results of the study that had the best treatment were reviewed from the quality requirements of dry tea, namely a drying temperature of 70 o C with a slice thickness of 3 mm. The results of the study proved that the best treatment was at a moisture content of 8.055%, ash content of 6.418%, hedonic test and color scoring of steeping herbal tea red dragon fruit skin is quite distinctive with values of 4.46 (likes) and 4.46 (yellowish red), hedonic test and shearing aroma of red dragon fruit skin herbal tea with a value of 4.13 (likes) and 4.46 is quite typical with dry tea products,  hedonic test and scoring on the taste of red dragon fruit skin herbal tea is worth 4.26 (likes) and 4.4 has a slightly astringent taste